Single-cell transcriptomic analysis of the tumor ecosystem of adenoid cystic carcinoma - Lin, Quanquan; Fang, Zhanjie; Sun, Jinlong; Chen, Fei; Ren, Yipeng; Fu, Zhenhong; Yang, Sefei; Feng, Lin; Wang, Feng; Song, Zhigang; Chen, Wei; Yu, Wenjun; et al. (Frontiers in Oncology, 2022)
Adenoid cystic carcinoma (ACC) is a malignant tumor that originates from exocrine gland epithelial cells. We profiled the transcriptomes of 49,948 cells from paracarcinoma and carcinoma tissues of three patients using single-cell RNA sequencing. Three main types of epithelial cells were identified from all cells, some of which altered with MYB family gene and EN1 transcriptomes were identified as premalignant cells. Developmental pseudo-time analysis showed that the premalignant cells eventually transformed into malignant cells. Furthermore, MYB and MYBL1 were found to belong to two different gene modules and were expressed in a mutually exclusive manner. The two gene modules drove ACC progression into different directions. Our ﬁndings provide novel evidence to explain the high recurrence rate of ACC and its characteristic biological behavior.